Rift Valley fever virus induces fetal demise in Sprague-Dawley rats through direct placental infection - McMillen, Cynthia M. (Sci Adv, 2018)
Rift Valley fever virus (RVFV) infections in pregnant livestock cause high rates of fetal demise; miscarriage in pregnant women has also been associated with RVFV infection. To address how RVFV infection during pregnancy causes detrimental effects on the fetus, we developed a pregnant rodent model of RVFV infection. We found that pregnant rats were more susceptible to RVFV-induced death than their nonpregnant counterparts and that RVFV infection resulted in intrauterine fetal death and severe congenital abnormalities, even in pups from infected asymptomatic pregnant rats. Virus distribution in infected dams was widespread, with a previously unrecognized preference for infection, replication, and tissue damage in the placenta. In human mid-gestation placental tissue, RVFV directly infected placental chorionic villi, with replication detected in the outermost syncytial layer. Our work identifies direct placental infection by RVFV as a mechanism for vertical transmission. This is the first study to show vertical transmission of RVFV with a lethal outcome in a species other than livestock. This study highlights the potential impact of a future epidemic of this emerging mosquito-borne virus.